Biochemistry-derived porous carbon-encapsulated metal oxide nanocrystals for enhanced sodium storage. (March 2016) - Zhou, Yanping; Sun, Wenping; Rui, Xianhong; Zhou, Yan; Ng, Wun Jern; Yan, Qingyu; Fong, Eileen
Abstract: Transitional metal oxides are promising anode materials for sodium ion batteries (SIBs) due to their high theoretical capacities and material abundance; however, their sodium storage capability is significantly hindered by the sluggish sodiation/desodiation reaction kinetics. Herein, towards achieving fast and durable sodiation/desodiation reaction, Fe3 O4 and Co3 O4 nanocrystals encapsulated in carbon micro-spheres are synthesized via a biochemistry approach using recombinant elastin-like polypeptides containing hexahistidine tag (ELP16-His) followed by annealing. Fe3 O4 and Co3 O4 nanocrystals of approximately 5 nm in size, which are uniformly dispersed in a carbon matrix, are obtained. The carbon-encapsulated metal oxides exhibit encouraging sodium storage capacities (657 and 246 mA h g −1 at 0.1 and 2 A g −1, respectively, for carbon-encapsulated Fe3 O4 ; 583 and 183 mA h g −1 at 0.1 and 2 A g −1, respectively, for carbon-encapsulated Co3 O4 ), and have a high capacity retention after 100 cycles at 0.5 A g −1 . The superior electrochemical properties of the carbon-encapsulated metal oxide nanocrystals demonstrate their potential for use as anode materials for high-capacity, high-rate and durable sodium storage. Graphical abstract: Highlights: A general biochemistry way was developed to prepare carbon-encapsulated metal oxides. Porous carbon-encapsulated Fe3 O4 and Co3 O4 nanocrystals (5 nm) were prepared. The carbon-encapsulated Fe3 O4 and Co3 O4 exhibited enhanced sodium storage capability.